Over-the-Counter Tooth Whitening Agents: A Review of Literature - Naidu,Arti. S. (2020)
Abstract There is an increased accessibility of over-the-counter (OTC) whitening agents with very little data in the literature regarding their effectiveness. This review was done to determine their effectiveness of the predominant OTC whitening agents from 2006 until 2018 where a comparison of each agent was made with a placebo, no treatment or with other OTC whitening agents. The major categories of OTC whitening agents such as dentifrices, whitening strips and paint on gels. Dentist prescribed bleaching applied at home and in-office bleaching studies and studies that demonstrated whitening products to participants were excluded. Articles were searched for in the databases of Medline (Ovid), PubMed, the Cochrane Library and Cochrane Central Register of Controlled Trials. Twenty-four articles were included in the systematic review and the quality of studies was determined by the GRADE (Grading of Recommendations, Assessment, Development and Evaluations) ranking criteria. Compared to other OTC, strips are reported to be effective. Two studies determined whitening strips to be effective. Whitening strips have been shown to be effective when compared with placebos and other OTC whitening agents. Dentifrices are effective in changing the shade of the tooth “by removing extrinsic stains” when compared to a placebo and non-whitening dentifrices, but they are not as effective in comparison to whitening strips. There is a lack of evidence with regards to the effectiveness of paint-on gels. While there is some evidence that OTC can alter shade in the short term, there is a need for better-designed studies.